1999
DOI: 10.1177/0743558499142002
|View full text |Cite
|
Sign up to set email alerts
|

Academic Functioning and Mental Health in Adolescence

Abstract: The current study examines patterns of academic functioning and mental health in 184 middle school children and the relation of such patterns to their prior and subsequent functioning. Data were collected from children during their second, third, fourth, eighth, and ninth grade school years. Cluster analyses were used to delineate patterns of academic functioning and mental health during eighth grade. The authors examined the relation of these patterns to academic functioning and mental health 1 year later the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(62 citation statements)
references
References 44 publications
5
56
0
1
Order By: Relevance
“…They have been often associated with negative outcomes such as decreased academic value and interest, decreased mastery goals, increased stress, and lower academic achievement Isakson & Jarvis, 1999;Roeser, Eccles, & Freedman-Doan, 1999;Rudolph, Lambert, Clark, & Kurlakowsky, 2001;Wigfield, Eccles, Schiefele, Roeser, & DavisKean, 2006). The fit between the person (student) and the environment (school) is a crucial factor affecting student's school adjustment and well-being during an educational transition.…”
Section: Introductionmentioning
confidence: 95%
“…They have been often associated with negative outcomes such as decreased academic value and interest, decreased mastery goals, increased stress, and lower academic achievement Isakson & Jarvis, 1999;Roeser, Eccles, & Freedman-Doan, 1999;Rudolph, Lambert, Clark, & Kurlakowsky, 2001;Wigfield, Eccles, Schiefele, Roeser, & DavisKean, 2006). The fit between the person (student) and the environment (school) is a crucial factor affecting student's school adjustment and well-being during an educational transition.…”
Section: Introductionmentioning
confidence: 95%
“…Under this "psychosocial" model, the effects of perceived discrimination on academic achievement are serially mediated, first through psychological adjustment, and then through school adjustment. The findings provide further support for studies that have demonstrated associations between perceived discrimination and psychological adjustment (e.g., Banks et al, 2006;Derluyn, Broekaert, & Schuyten, 2008;Seaton et al, 2008), between psychological and school adjustment (Hawker & Boulton, 2000;Roeser et al, 1999Roeser et al, , 1998Rueger & Jenkins, 2014), and between school adjustment and academic achievement (Dotterer & Lowe, 2011;Totura et al, 2014). In elucidating a pathway through which perceived discrimination likely hampers achievement, this model accentuates the potentially protective roles of psychological adjustment and school adjustment.…”
Section: Discussionmentioning
confidence: 51%
“…The model is consistent with a motivational deficit account of school failure: Receipt of perceived discrimination at school may lead to a lowering of expectancy beliefs, less ambitious goal-setting, reduced on-task behavior, and/or lower persistence levels (Al Ramiah et al, 2010;Roeser et al, 1999). It may even be manifested in self-defeating and self-handicapping behaviors, in accord with a learned helplessness explanation of school maladjustment (Maier & Seligman, 1976).…”
Section: Perceived Discrimination and Academic Achievement: Mediated mentioning
confidence: 58%
See 2 more Smart Citations